Fangirl - Rowell, Rainbow (London : Macmillan, 2013)
Being fans of the Simon Snow series helped Cath and her twin sister, Wren, cope as girls whose mother left them, but now, as they move through college, Cath feels unready to live without Wren holding her hand--and without her passion for Snow.
"Based on the bestselling novel by Rainbow Rowell"
Keywords: Graphic novels; Fans (Persons) -- Fiction; Authorship -- Fiction; Universities and colleges -- Fiction; Twins -- Fiction; Sisters -- Fiction; Coming of age -- Fiction; COMICS & GRAPHIC NOVELS / Manga / School Life; YOUNG ADULT FICTION / Comics & Graphic Novels / Manga; Coming-of-age comics; Romance comics; Graphic novel adaptations; Manga